FATWA SEBAGAI MEDIUM COUNTER-TERRORISME - Mohd Anuar Bin Ramli; Rahimin Affandi Abdul Rahim; Muhd Imran Abdul Razak; Muhammad Yusri Yusof Salleh; Paiz Hasan; Muhammad Izzul Syahmi Zulkepli (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2018)
Fatwa has proven to play a significant role in the history of Islamic law. From the legal view of a personal matter until it is formalized, the role of fatwa is crucial to the community as it has either positive or negative impacts.There is no exception to religious extremism, the fatwa of certain figures has influenced individual psychology and beliefs or groups committed to acts of terrorism. As for the opposing parties, various fatwa have also been issued to deal with such extremism. Based on these facts, this study examines the weakness of fatwa as a medium of counter religious terrorism. By using a full qualitative methodology, documentation data related to this study are analyzed inductively, deductively and comparative. The findings show that extremist groups have used fatwa methods to develop their ideology and influence. In addition, various parties including Western scholars have realized the importance of fatwas as counter-ideological tools, but the study found that there is still room for fatwa improvement such as more detailed ideological justification, consistency in fatwa and even justice in its contents. Fatwa telah terbukti memainkan peran penting dalam sejarah hukum Islam. Dari pandangan hukum masalah pribadi sampai diformalkan, peran fatwa sangat penting bagi masyarakat karena memiliki dampak positif atau negatif. Tidak ada pengecualian untuk ekstremisme agama, fatwa tokoh-tokoh tertentu telah mempengaruhi psikologi dan keyakinan individu. atau kelompok-kelompok yang berkomitmen terhadap tindakan terorisme. Sedangkan untuk partai-partai oposisi, berbagai fatwa juga telah dikeluarkan untuk menghadapi ekstremisme semacam itu. Berdasarkan fakta-fakta ini, penelitian ini menguji kelemahan fatwa sebagai media kontra terorisme agama. Dengan menggunakan metodologi kualitatif penuh, data dokumentasi yang terkait dengan tema penelitian dianalisis secara induktif, deduktif dan komparatif. Temuan menunjukkan bahwa kelompok ekstrimis telah menggunakan metode fatwa untuk mengembangkan ideologi dan pengaruh mereka. Selain itu, berbagai pihak termasuk sarjana Barat telah menyadari pentingnya fatwa sebagai alat kontra-ideologi, tetapi studi ini menemukan bahwa masih ada ruang untuk peningkatan fatwa seperti pembenaran ideologis yang lebih rinci, konsistensi dalam fatwa dan bahkan keadilan dalam isinya.